Mindfulness and mechanisms of attention in a neutral and palatable food context - Logemann-Molnár, Zsófia; Veres-Székely, Anna; Demetrovics, Zsolt; Logemann, H. N. Alexander (Frontiers in Psychology, 2024)
Mindfulness has been associated with benefits on cognitive processes, including attention. However, the exact relationship between mindfulness, components of attention, and the role of reward context has not yet been fully elucidated, which is relevant, especially in the context of addiction. In the current study, we specifically evaluated the relationship between dispositional mindfulness and the balance between voluntary (top-down), and stimulus-driven (bottom-up) attention. In addition, we explored whether the relationship was mediated by asymmetry of frontal brain activity, an index of approach tendencies, and varies as a function of reward context. In total, 95 participants (30 male, 65 female) with a mean age of 25.87 (SD = 7.38) participated. Resting-state electrophysiological activity was recorded using EEG, and participants were assessed on dispositional mindfulness, and performed the visuospatial cueing (VSC) task, which indexed voluntary-and stimulus-driven attention in a neutral and palatable food (reward) context. In the endogenous VSC task, a central cue signals the likely location of a Mindfulness and mechanisms of attention 2 subsequent target. The validity effect represents the benefit of valid cueing relative to the costs of invalid cueing in terms of response time. Results showed that dispositional mindfulness was associated with a reduced validity effect, plausibly reflecting a combination of reduced voluntary attention and increased stimulus-driven attention, irrespective of condition. The relationship between dispositional mindfulness and visuospatial attention could not be explained by asymmetry of frontal brain activity.